Distinct Changes in CREB Phosphorylation in Frontal Cortex and Striatum During Contingent and Non-Contingent Performance of a Visual Attention Task - Carli, Mirjana; Pozzi, Laura; Sacchetti, Giuseppina; Agnoli, Laura; Mainolfi, Pierangela; Invernizzi, Roberto W. (Frontiers in Behavioral Neuroscience, 2011)
The cyclic-AMP response element binding protein (CREB) family of transcription factors has been implicated in numerous forms of behavioural plasticity. We investigated CREB phosphorylation along some nodes of corticostriatal circuitry such as frontal cortex (FC) and dorsal (caudate putamen, CPu) and ventral (nucleus accumbens, NAC) striatum in response to the contingent or non-contingent performance of the five-choice serial reaction time task (5-CSRTT) used to assess visuospatial attention. Three experimental manipulations were used; an attentional performance group (contingent, “master”), a group trained previously on the task but for whom the instrumental contingency coupling responding with stimulus detection and reward was abolished (non-contingent, “yoked”) and a control group matched for food deprivation and exposure to the test apparatus (untrained). Rats trained on the 5-CSRTT (both master and yoked) had higher levels of CREB protein in the FC, CPu and NAC compared to untrained controls. Despite the divergent behaviour of “master” and “yoked” rats CREB activity in the FC was not substantially different. In rats performing the 5-CSRTT (“master”), CREB activity was completely abolished in the CPu whereas in the NAC it remained unchanged. In contrast, CREB phosphorylation in CPu and NAC increased only when the contingency changed from goal-dependent to goal-independent reinforcement (“yoked”). The present results indicate that up-regulation of CREB protein expression across cortical and striatal regions possibly reflects the extensive instrumental learning and performance whereas increased CREB activity in striatal regions may signal the unexpected change in the relationship between instrumental action and reinforcement.